Report on small-scale mechanization opportunities for feed and forage production in Mali - Rudiger, Udo; Idoudi, Zied; Sow, Amadou; Sacko, Idrissa (2023)
The report shows the results of this 2-week survey, including feed processing machines available in Mali (imported and manufactured) and farmer organizations and innovation platforms involved in feed business